Principal component analysis in wild Apis mellifera L. (Hymenoptera: Apidae) wings from Trujillo, Laredo, Casa Grande and Viru. La Libertad, Peru - Rodríguez Rodríguez, Roberto; Facultad de Ciencias Biológicas, Universidad Nacional de Trujillo (2023)
Geometric morphometry abstracts the shape of organisms by using reference points, quantifiesand analyzes the morphological variation of different species. The objective of this work was todetermine the population structure of wild bees Apis mellifera L. from Trujillo, Laredo, Casa Grandeand Viru, by means of principal component analysis; samples of nurse worker bees were collectedfrom November 2019 to March 2020 and preserved in 70% alcohol, then they were transferredto the Entomology laboratory of the Faculty of Biological Sciences of the National University ofTrujillo, the right mesothoracic wings were mounted and images of these were taken in JPG format,with the Samsung J6PLUS cell phone camera calibrated with the Euromex stereoscope. An HPIntel Core i5 laptop was used and a tps file of the images was created using tpsUtil64 version 1.81software; then with tpsDig2 version 2.32, 19 anatomical reference points were placed, convertedinto coordinates in a two-dimensional plane and saved in the same file; then, MorphoJ software wasused and procrustes and principal component analyses were performed. The first two componentswere found to explain 30.85% of the cumulative variance, the first with 17.34% and the second with13.51%, with a significant overlap between the bees of the four locations, there is no significantdifference between the negative end of PC1 and the positive end of PC1 according to the deformedwing contour diagrams. Principal component analysis shows that the investigated wild A. melliferacolonies are genetically very homogeneous.